Influence of metal hydride hollow cathode on Penning ion source operation - Sereda, I.; Ryabchikov, D.; Hrechko, Ya.; Babenko, Ie. (Вопросы атомной науки и техники, 2021)
The influence of metal hydride hollow cathode on a Penning ion source operation has been carried out. The feature of investigation is hydrogen injection only due to its desorption from metal hydride under ion-stimulated processes. The regimes of optimal discharge operation in the hollow cathode mode are determined. It has been revealed that the transition to the hollow cathode mode occurs at lower voltages, the discharge works without external gas supply, and the working pressure in the cell is set at the level determined by the discharge current. The supply of a negative bias to the metal hydride hollow cathode weakly affects the features of the emission of axial particles, although it allows the increase of plasma density near the metal hydride hollow cathode. Досліджено вплив металогідридного порожнистого катода на роботу джерела іонів Пеннінгa. Особливістю дослідження є інжекція водню тільки за рахунок його десорбції з металогідриду під дією іонно-стимульованих процесів. Визначено режими оптимальної роботи розряду в режимі порожнистого катода. Виявлено, що перехід у режим порожнистого катода відбувається при більш низькій напрузі, розряд працює без зовнішньої подачі газу, а робочий тиск в осередку встановлюється на рівні, що визначається струмом розряду. Подача негативного зсуву на порожнистий катод з гідриду металу слабо впливає на особливості емісії аксіальних частинок, хоча дозволяє збільшити щільність плазми поблизу металогідридного порожнистого катода. Исследовано влияние металлогидридного полого катода на работу источника ионов Пеннинга. Особенностью исследования является инжекция водорода только за счет его десорбции из металлогидрида под действием ионно-стимулированных процессов. Определены режимы оптимальной работы разряда в режиме полого катода. Выявлено, что переход в режим полого катода происходит при более низких напряжениях, разряд работает без внешней подачи газа, а рабочее давление в ячейке устанавливается на уровне, определяемом током разряда. Подача отрицательного смещения на полый катод из гидрида металла слабо влияет на особенности эмиссии аксиальных частиц, хотя позволяет увеличить плотность плазмы вблизи металлогидридного полого катода.